A 1916 World War I notebook of Luigi Sacco. Issue 3 (4th May 2018) - Bonavoglia, Paolo
ABSTRACT: Letters, notes, and above all an original notebook by Luigi Sacco dated 1916 have shed new light on the establishment and development of the "Ufficio (or Reparto) Crittografico" of the Italian Army Headquarters in World War I. Three decrypted messages, unpublished until now, are included with Sacco's comments.